The efficacy of statins for improving cognitive impairments in pediatric patients with neurofibromatosis type 1 (NF-1): a meta-analysis - Gan, Lutong; Zhu, Weiwen; Fu, Pengqing (Frontiers in Pediatrics, 2023)
Background: Given the considerable discrepancies in the evidence concerning the efficacy of statins in ameliorating cognitive impairments in pediatric patients with Neurofibromatosis Type 1 (NF-1), this study conducts a systematic review and meta-analysis to consolidate existing evidence to evaluate the efficacy of statins on cognitive impairments in children with NF-1. Methods: This study adhered to the PRISMA statement, and the research protocol was pre-registered on PROSPERO (#CRD: 42022369072). Comprehensive searches of databases including PubMed, Embase, and the Cochrane Library were performed up to March 31, 2023 to identify randomized controlled trials (RCTs) investigating the effects of statins on cognitive impairments in children with NF-1. Statistical analyses were conducted using Review Manager 5.4.1. A fixed- or random-effects model was employed according to the I² statistic. As all data were continuous, MD [95% CI] was used as the pooled estimate. Results: The final analysis included five RCTs with a total of 364 patients. The meta-analysis indicated that aside from a statistically significant improvement in internalizing problems (MD [95%CI] = 3.61[0.11, 7.10], P= 0.04)、Object assembly Test (MD [95%CI] = 0.53[0.12, 0.93], P= 0.01)、Cancellation Test (MD [95%CI] = 3.61[0.11, 7.10], P＜0.0001), statins did not exhibit significant efficacy in improving other cognitive aspects in children with NF-1 (P>0.05). An additional descriptive analysis on indices that cannot be meta-analyzed revealed considerable inconsistency in the therapeutic effect of statins across different studies. Conclusion: Current evidence suggests that statins may not be effective for cognitive performance in children with NF-1.